(untitled) (Ágora de Heterodoxias, 2024)
The objective of the book under analysis is to identify the stages of the process of designing and implementing public policies, from the conceptual framework to the prescriptive framework; each chapter presents a wide range of authors and literature to understand each stage, with recommendations, mechanisms and instruments for everyone, the analyst, the executing professional or the public authority. This makes it possible to have a multidisciplinary approach at hand, so that different actors can take into account concepts, techniques, quantitative and qualitative research methods, and identify the public problem, so that it can be escalated to a government agenda to be addressed by the current authority. Current governments, in this post-modern era, face the challenge of developing more efficient and effective public policies, with greater and broader citizen participation in public policies. In these, in particular, it is considered that the book reviewed achieves its objective.